Chemo-Protective Potential of Cerium Oxide Nanoparticles against Fipronil-Induced Oxidative Stress, Apoptosis, Inflammation and Reproductive Dysfunction in Male White Albino Rats - Hamida Saleh; Atef M. K. Nassar; Ahmed E. Noreldin; Dalia Samak; Norhan Elshony; Lamiaa Wasef; Yaser H. A. Elewa; Shaimaa M. A. Hassan; Abdullah A. Saati; Helal F. Hetta; Gaber El-Saber Batiha; Masakazu Umezawa; et al. (Molecules, 2020)
Fipronil (FIP) is an insecticide commonly used in many fields, such as agriculture, veterinary medicine, and public health, and recently it has been proposed as a potential endocrine disrupter. The purpose of this study was to inspect the reproductive impacts of FIP and the possible protective effects of cerium nanoparticles (CeNPs) on male albino rats. Rats received FIP (5 mg/kg bwt; 1/20 LD50), CeNPs (35 mg/kg bwt) and FIP+CeNPs per os daily for 28 days. Serum testosterone levels, testicular oxidative damage, histopathological and immunohistochemical changes were evaluated. FIP provoked testicular oxidative damage as indicated by decreased serum testosterone (≈60%) and superoxide dismutase (≈50%), glutathione peroxidase activity (≈46.67%) and increased malondialdehyde (≈116.67%) and nitric oxide (≈87.5%) levels in testicular tissues. Furthermore, FIP induced edematous changes and degeneration within the seminiferous tubules, hyperplasia, vacuolations, and apoptosis in the epididymides. In addition, FIP exposure upregulated interleukin-1β (IL-1β), nitric oxide synthase 2 (NOS), caspase-3 (Casp3) and downregulated the Burkitt-cell lymphomas (BCL-2), inhibin B proteins (IBP), and androgen receptor (Ar) mRNA expressions Casp3, nitric oxide synthase (iNOS), ionized calcium-binding adapter molecule 1(IBA1), and IL-1β immunoreactions were increased. Also, reduction of proliferating cell nuclear antigen (PCNA), mouse vasa homologue (MVH), and SOX9 protein reactions were reported. Interestingly, CeNPs diminished the harmful impacts of FIP on testicular tissue by decreasing lipid peroxidation, apoptosis and inflammation and increasing the antioxidant activities. The findings reported herein showed that the CeNPs might serve as a supposedly new and efficient protective agent toward reproductive toxicity caused by the FIP insecticide in white male rats.